A NEW PERSPECTIVE ON TIMES: A LITERATURE REVIEW ON THE HISTORY OF COMMITTEES OF IMPOVERISHED PEASANTS (Південний архів (історичні науки), 2024)
The article analyzes the achievements of domestic historiography in studying the history of Committees of Poor Peasants of the Ukrainian Soviet Socialist Republic (CPP USSR) during the period from 1920 to 1933. The author emphasizes that the role of Ukrainian poor peasantry in the socio-political and socio-economic life of Soviet villages is predominantly depicted within the framework of the outdated Soviet paradigm. The analysis of historiographical heritage convinces that Soviet historiography has established a mistaken tradition of viewing the village and peasantry in the coordinates of the history of communism construction. Accordingly, the purpose of the article lies in a critical analysis of scientific literature, highlighting achievements, shortcomings, and miscalculations, as well as substantiating a new approach to studying the problem of CPP history within the formation of a new concept of domestic history. The methodological toolkit is based on considering the historiographical situation, respectful treatment of predecessors' work with subsequent identification of methodological approaches, involvement of source base and methods of identifying, grouping, and critically using the main groups of sources, justification of conclusions, originality, and contribution to the historical reconstruction of CPP history. At the same time, the article's historiographical analysis takes into account the dominant contemporary trends in evaluating socio-political, economic, and cultural processes in the environment of Ukrainian peasantry from the 1920s to the early 1930s, including the role of CPP in the Holodomor of 1932–1933. Understandably, works of post-Soviet times are more thoroughly analyzed. The main results of the study of CPP USSR emphasize the necessity of an anthropocentric approach to this topic. Traditional historiography focuses on political and economic narratives but largely ignores social and cultural aspects. Shortcomings of Soviet historical science, such as solely using the Marxist-Leninist approach, somewhat complicate a comprehensive objective understanding of reality. However, modern Ukrainian historiography has created new opportunities for studying the history of Ukrainian peasantry, including Committees of Poor Peasants. In conclusion, based on the reviewed literature, periods of CPP history research from its creation to the present day are analyzed. Emphasis is placed on the obsolescence of traditional approaches in historiography and the need for a new concept that will consider the study of peasants, their values, attitudes, and participation in CPP.
Keywords: Holodomor, historiography, CPP, new concept, peasantry, social history.